2022
DOI: 10.1021/acs.chemmater.1c04015
|View full text |Cite
|
Sign up to set email alerts
|

Lattice-Directed Selective Synthesis of Acetylenic and Diacetylenic Organometallic Polyynes

Abstract: As a bottom-up strategy, on-surface synthesis shows great potential in constructing novel carbon-based nanostructures. Herein, on-surface reactions of 1,1,2,2-tetraiodoethylene and 1,1,4,4-tetrabromo-1,2,3-butatriene were systematically explored. A combination of scanning tunneling microscopy and noncontact atomic force microscopy demonstrates that it is feasible to achieve acetylenic and diacetylenic organometallic polyyne (i.e., acetylenic Ag−carbyne and diacetylenic Cu−carbyne) on Ag(110) and Cu(110) surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…CBr 4 monomers (as sketched in Figure 1a) were deposited on the clean Cu(110) single-crystal surface held at 300 K by thermal sublimation (with a typical sublimation temperature of 300 K) under ultra-high vacuum conditions, resulting in the formation of isolated 1D chain structures along the closepacked [11̅ 0] direction of the substrate (Figure 1b). Based on our previous studies, 20,24 these chain structures with a periodicity of 5.2 ± 0.2 Å (Figure 1b) could be naturally attributed to Cu-incorporated metalated carbyne (−Cu−C� C−), and the protrusions within the chain result from the electronic density of states of Cu atoms. Notably, organometallic species are often formed in dehalogenative coupling reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…CBr 4 monomers (as sketched in Figure 1a) were deposited on the clean Cu(110) single-crystal surface held at 300 K by thermal sublimation (with a typical sublimation temperature of 300 K) under ultra-high vacuum conditions, resulting in the formation of isolated 1D chain structures along the closepacked [11̅ 0] direction of the substrate (Figure 1b). Based on our previous studies, 20,24 these chain structures with a periodicity of 5.2 ± 0.2 Å (Figure 1b) could be naturally attributed to Cu-incorporated metalated carbyne (−Cu−C� C−), and the protrusions within the chain result from the electronic density of states of Cu atoms. Notably, organometallic species are often formed in dehalogenative coupling reactions.…”
Section: ■ Results and Discussionmentioning
confidence: 78%
“…Intriguingly, the asymmetric DOS for spin-up and spindown components indicates a spin polarization of the CuCRs, although the incorporated Cu atoms in the chains are not magnetically active, which is similar to our previous studies. 24 More interestingly, the CuCRs exhibit a width-dependent band gap modulation. The calculated band gap decreases from 4.02 to 2.38 eV with an increasing width (N) from 1 to 5 (Figure 3a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(a)), where m and n represent the spacer group and the terminal alkyl chain around the DA units, respectively. We showed that the columnar packing of HBC cores can help align the DA-containing side chains along the column and get polymerized [26][27][28][29][30] to give conjugated poly(eneyne) chains as conducting channels for transistor application. The position of the DA unit along the alkyl chain nevertheless appeared to affect the polymerization profoundly.…”
Section: Introductionmentioning
confidence: 99%
“…On-surface synthesis is emerging as a promising approach for atomically precise fabrication of highly reactive 1D nanostructures with sp-hybridization that could be hardly synthesized via conventional solution synthetic chemistry [19][20][21][22] . Developments in scanning tunneling microscopy (STM) and atomic force microscopy (AFM) have enabled the designing and in-situ characterization of low-dimensional carbon nanostructures with unprecedented resolution on the atomic scale and chemical-bond level [23][24][25] .…”
Section: Introductionmentioning
confidence: 99%